2022
DOI: 10.1177/00207640221141018
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and sociocultural correlates of post-traumatic stress disorder and complex PTSD among Chinese community health service users in Hong Kong

Abstract: Objectives: Complex post-traumatic stress disorder (CPTSD) is a newly recognized trauma disorder in ICD-11. Little is known about the prevalence and correlates of CPTSD in primary care settings. Its cultural aspects also remained minimally explored. This study investigated the prevalence and sociocultural correlates of PTSD and complex PTSD among Chinese community health service users in Hong Kong. Methods: This study investigated ICD-11 PTSD and CPTSD in a sample of adults ( N = 376) who had recently received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Therefore, early identification and management of trauma-related symptoms are important. It should be noted that trauma-related conditions are frequently overlooked in clinical settings, as evidenced by previous research (Cusack et al, 2006 ; Fung, Wong, Lam, Chien, Hung, Ross, et al, 2022 ). In our sample, only 36 participants (23.7%) self-reported a previous clinical diagnosis of PTSD/complex PTSD.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Therefore, early identification and management of trauma-related symptoms are important. It should be noted that trauma-related conditions are frequently overlooked in clinical settings, as evidenced by previous research (Cusack et al, 2006 ; Fung, Wong, Lam, Chien, Hung, Ross, et al, 2022 ). In our sample, only 36 participants (23.7%) self-reported a previous clinical diagnosis of PTSD/complex PTSD.…”
Section: Discussionmentioning
confidence: 90%
“…Third, informed by previous studies showing that post-traumatic and dissociative symptoms/disorders are associated with more impairments and/or healthcare costs in both psychiatric and nonpsychiatric samples (as these symptoms are less likely to respond well to standard, non-trauma-specific treatments) (e.g. Fung, Wong, Lam, Chien, Hung, Ross, et al, 2022 ; Gonzalez Vazquez et al, 2017 ; Myrick, Webermann, Langeland, et al, 2017 ; Ross & Dua, 1993 ), we also examined whether participants with PTSD or elevated levels of dissociation would be more likely to report use of psychiatric hospitalization and psychiatric emergency services.…”
Section: Introductionmentioning
confidence: 99%
“…Only participants who self-reported that they had been diagnosed with a learning or reading disorder, dementia, and/or cognitive impairments were excluded. The methodology, sampling and results of the study have been reported elsewhere [ 14 ]. In Sample 2, N = 377 Hong Kong community health (TCM) service users participated in the web-based survey.…”
Section: Methodsmentioning
confidence: 99%
“…To investigate trauma and trauma-related mental health problems among community health service users in Hong Kong, we recruited a sample of traditional Chinese medicine (TCM) service users to participate in a survey study. Part of the data has been reported elsewhere (Fung, Wong, Lam, Chien, Hung, & Ross, 2022 ; Fung, Wong, Lam, Chien, Hung, Ross, et al, 2022 ; Po et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%